Peningkatan Kemampuan Bahasa Siswa Melalui Kegiatan Membaca Permulaan Dengan Menggunakan Kartu Bergambar di Kelompok B TK Santa Thersesia I Pangkalpinang - Bernadet Sepryyana (Jurnal Pendidikan Tuntas, 2023)
The low level of early reading skills is the background of why this research was conducted, so this study aims to improve early reading skills through the letter card game method in group B of Theresia I Pangkalpinang Kindergarten. This study used the subject of group B students of Theresia I Kindergarten totaling 18 people. The object of research focuses on improving the ability to read beginning through the method of playing letter cards. The data collection method used checklist observation, interviews and documentation. The results showed that there was an increase in early reading skills by 22.2% at the end of cycle I and at the end of cycle II an increase of 49.9%. This improvement in early reading skills can be seen from students being able to read pictures, being able to point and point to the letter symbols requested, being able to read simple words and sound the letters in the word, being able to connect pictures with words, being able to arrange letters into meaningful words and, being able to group vowels and consonants. The implementation steps used to improve students' beginning reading skills are by using group competition games, the teacher provides an explanation of the alphabet, and giving verbal awards and applause to the winning group. Keywords: Language skills, beginning reading, letter card game method